2011
DOI: 10.2478/s11756-011-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of α-galactosidase cDNA from Penicillium janczewskii zaleski

Abstract: In recent years, α-galactosidase has been attracting more and more attention because of its potential applications in many aspects. Using reverse transcription-polymerase chain reaction and rapid amplification of cDNA ends, a full-length cDNA sequence composed of 2,439 bp was cloned from Penicillium janczewskii zaleski and was subcloned into pPICZαA and transformed into Pichia pastoris strain X-33. In a 10-L fermentor, the recombinant yeast expressed α-galactosidase with a yield of 254 U/mL by methanol inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our previous study, even at static conditions, germination of conidia was only observed in three out of the eight fungal strains tested (Frija et al, 2011 ). Several studies support the catabolic potential of P. janczewskii , e.g., for producing secondary metabolites (Madi and Katan, 1998 ), exo-inulinases (Pessoni et al, 2007 ), xylanases (Terrasan et al, 2010 , 2016 , 2017 ), and galactosidases (Zhang et al, 2011 ), as well as its ecological relevance in modulating plant–fungi interactions, either antagonizing (Madi and Katan, 1998 ) or stimulating (Kwasna, 2004 ) important plant pathogenic fungi.…”
Section: Discussionmentioning
confidence: 92%
“…In our previous study, even at static conditions, germination of conidia was only observed in three out of the eight fungal strains tested (Frija et al, 2011 ). Several studies support the catabolic potential of P. janczewskii , e.g., for producing secondary metabolites (Madi and Katan, 1998 ), exo-inulinases (Pessoni et al, 2007 ), xylanases (Terrasan et al, 2010 , 2016 , 2017 ), and galactosidases (Zhang et al, 2011 ), as well as its ecological relevance in modulating plant–fungi interactions, either antagonizing (Madi and Katan, 1998 ) or stimulating (Kwasna, 2004 ) important plant pathogenic fungi.…”
Section: Discussionmentioning
confidence: 92%
“…Contrary to our results, the α-galactosidase from Penicillium sp. F63 CGMCC 1669 [ 16 ] and Penicillium janczewskii zaleski [ 27 ] had optimum activity in the acidic pH range. The neutral or weak alkaline pH form of α-galactosidase is suitable for the hydrolysis of soy milk, since an acidic pH leads to the deposition of soy protein and gives milk its sour taste [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the theoretical molecular weight of T26GAL was determined to be 83.47 kDa, which is consistent with that of the previously reported GH36 family α-galactosidases, such as the 82.9 kDa α-galactosidase from Gibberella sp. F75 [ 29 ] and the 81.8 kDa α-galactosidase isolated from P. janczewskii zaleski [ 28 ]. Homology-modeling using Swiss-Model showed that the 3D structure of T26GAL was similar to the α-galactosidases from L. acidophilus and Thermotoga maritima .…”
Section: Discussionmentioning
confidence: 99%